Socio-climatic hotspots in Brazil - Torres, Roger R.; Lapola, David M. [UNESP]; Marengo, Jose A.; Lombardo, Magda A. [UNESP] (Springer, 2012)
Brazil suffers yearly from extreme weather and climate events, which can be exacerbated in a warmer climate. Although several studies have analyzed the projections of climate change in Brazil, little attention has been paid to defining the locations that can be most affected, and consequently have a more vulnerable population, in a spatially-explicit form. This study presents a spatial analysis of summarized climate change data and a joint investigation combining these possible climate changes and social vulnerability indicators in Brazil. The Regional Climate Change Index (RCCI), which can synthesize a large number of climate model projections, is used for the climate analysis, and the Socio-Climatic Vulnerability Index (SCVI) is proposed to aggregate local population vulnerabilities to the climate change information. The RCCI results show climatic hotspots emerging in Brazil, covering the western portion of the Northeast (NE), northwestern Minas Gerais state and center-western (CW) and northern regions (N), except northeast Para and Amapa states. The SCVI analysis reveals major socio-climatic hotspots in the NE and several localized hotspots in some of the major Brazilian metropolitan regions, namely Manaus, Belo Horizonte, Brasilia, Salvador, Rio de Janeiro and So Paulo. The two novelties of this study are a spatially detailed analysis of the RCCI in Brazil and the development of an index that can summarize the large amount of climate model information available today with social vulnerability indicators. Both indices may be important tools for improving the dialogue between climate and social scientists and for communicating climate change to policymakers in a more synthetic and socially relevant form.